2018
DOI: 10.1038/nbt.4060
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore sequencing and assembly of a human genome with ultra-long reads

Abstract: We report the sequencing and assembly of a reference genome for the human GM12878 Utah/Ceph cell line using the MinION (Oxford Nanopore Technologies) nanopore sequencer. 91.2 Gb of sequence data, representing ~30× theoretical coverage, were produced. Reference-based alignment enabled detection of large structural variants and epigenetic modifications. De novo assembly of nanopore reads alone yielded a contiguous assembly (NG50 ~3 Mb). Next, we developed a protocol to generate ultra-long reads (N50 > 100kb, up … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
1,586
3
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,652 publications
(1,682 citation statements)
references
References 66 publications
24
1,586
3
7
Order By: Relevance
“…We observed that the errors tend to occur between purines or between pyrimidines, probably because they have similar chemical structures 11 . In addition, we also observed that substitution errors tend to occur at the same nucleotide position across repeats (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…We observed that the errors tend to occur between purines or between pyrimidines, probably because they have similar chemical structures 11 . In addition, we also observed that substitution errors tend to occur at the same nucleotide position across repeats (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 84%
“…The advantage of the nanopore sequencer over the PacBio sequencer is the ultra-long read capability 11 . It has the potential to obtain reads of more than 100 kbp, the approximate mean size of D4Z4 in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative approach may be to use nanopore sequencers to directly read different modifications from the DNA (Burgess 2017; Schatz 2017). Nanopore sequencing uses pores through which nucleic acid strands are Bpulled^and the ionic pattern reveals the nucleotide sequence, including modifications (Jain et al 2017;Shendure et al 2017). These technologies are still in the developmental phase but show great promise (Rand et al 2017).…”
Section: Alternatives To Conversion-based Sequencingmentioning
confidence: 99%